Departing from anonymous and quantitative student feedback: Fostering learning and teaching development through student evaluations (Journal of Applied Learning and Teaching, 2020)
The Police Studies program at the University of Tasmania (UTAS), Australia has been growing exponentially since 2015. Since then, UTAS became the only Australian university teaching police across several jurisdictions. One key to this success has been the improvement of teaching and learning via an incremental yet drastically altered approach to student experience and feedback. In 2017, rather than relying on student evaluations that were not engaging individuals positively, innovative and alternative means were sought to ensure communication and feedback could contribute to teaching and learning development, as well as collaborative staff and student development. Student evaluations became qualitative only and fully identified. This radically changed the feedback provided to both police and UTAS lecturers teaching recruits at the police academy.This paper analyses the changes that occurred after teaching staff decided to completely depart from anonymous and quantitative student evaluations. Eighteen (18) police educators teaching at the Tasmania Police Academy (both police and UTAS staff) were invited to provide their views on those changes. Via an exploratory study of staff experience (67% surveys were returned), and in light of recent literature in tertiary education, we contest current assumptions about, and practice in, student feedback. Our approach arguably disputes traditional and historical thinking on the normative role and format of student data in evaluating the quality of a learning experience. We argue that this innovative, transparent and accountable feedback unlocks ways to embed students within curriculum improvement, teacher development, and learning experience.